2016
DOI: 10.1049/htl.2015.0058
|View full text |Cite
|
Sign up to set email alerts
|

Predicting asthma exacerbations employing remotely monitored adherence

Abstract: This Letter investigated the efficacy of a decision-support system, designed for respiratory medicine, at predicting asthma exacerbations in a multi-site longitudinal randomised control trial. Adherence to inhaler medication was acquired over 3 months from patients with asthma employing a dose counter and a remote monitoring adherence device which recorded participant's inhaler use: n = 184 (23,656 audio files), 61% women, age (mean ± sd) 49.3 ± 16.4. Data on occurrence of exacerbations was collected at three … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 15 publications
(7 citation statements)
references
References 30 publications
0
7
0
Order By: Relevance
“…However, self-report measures are prone to overestimation of adherence due to social desirability bias [ 68 ]. Dose-counters on inhalers are also used to measure adherence in trials but have been found to overestimate actual use compared with the use of a digital inhaler in practice [ 69 ]. While run-in periods and study design can lessen the influence of inhaler nonadherence on outcomes, the actual impact is unknown without the use of these digital devices throughout the study.…”
Section: Methodsmentioning
confidence: 99%
“…However, self-report measures are prone to overestimation of adherence due to social desirability bias [ 68 ]. Dose-counters on inhalers are also used to measure adherence in trials but have been found to overestimate actual use compared with the use of a digital inhaler in practice [ 69 ]. While run-in periods and study design can lessen the influence of inhaler nonadherence on outcomes, the actual impact is unknown without the use of these digital devices throughout the study.…”
Section: Methodsmentioning
confidence: 99%
“…My Asthma Portal enhances asthma quality of life but not asthma control [31]. Another study was able to predict asthma exacerbations using remotely monitored adherence [32].…”
Section: Clinical Decision Support Systems In the Management Of Complmentioning
confidence: 99%
“…Longitudinal data on patients' adherence collected via digital applications, particularly when supported by digitally collected information on symptoms and physiological and environmental parameters, can provide a detailed and precise basis for understanding an individual's disease [44, 45]. For example, in patients with asthma, digitally collected real-time data on adherence and symptoms can help HCPs differentiate between symptoms or changes in lung function due to low adherence versus those indicating refractory disease or disease progression [46].…”
Section: Potential Opportunities Provided By Digital Technologies In mentioning
confidence: 99%
“…A major strategy for improving health outcomes in respiratory patients is through decreasing the likelihood and magnitude of clinical deterioration, exacerbations and disease complications. Digitally collected patient data on physiology, patterns of medication adherence, trends in reliever usage and exposure to environmental pollution may identify “digital biomarkers” that help predict future exacerbations [41, 45, 57]. The use of newer data mining and analysis techniques leveraging growing mobile computing power holds particular promise to extract useful information from large datasets, as does the use of existing large and comprehensive databases as “training sets” for the development of prediction tools [58, 59].…”
Section: Potential Opportunities Provided By Digital Technologies In mentioning
confidence: 99%
See 1 more Smart Citation